Hábitos alimenticios y su relación con el índice de masa corporal en preescolares del Sector San Pablo del Cantón Santa Elena en el periodo de noviembre 2023 a abril de 2024. - Caicedo Bajaña, Erick Ariel (2024)
Currently, the eating habits of preschoolers are being modified according to advertising, fashion and the limited time that exists in homes for the preparation of healthy foods; in other cases, due to lack of resources and knowledge about healthy eating. The objective is to determine eating habits and their relationship with the body mass index in preschoolers in the San Pablo sector of the province of Santa Elena, during the period November 2023. The body mass index (BMI) is a number that is calculated based on the person's weight and height. The problem of nutrition in the childhood stage is not only reduced to malnutrition, since the habits acquired by children due to their family or social environment can also generate an effect towards the other end of the nutritional state, increasing their level. of adiposity with the consequent overweight and even obesity. Studies carried out by students from the State University of the Santa Elena Peninsula obtained results in 2019 such as that the rate of chronic malnutrition reached 37%, the only province in the coastal region above the national average, and the rate of overweight and Obesity was around 6.5%, below the national average. The role of nursing at the community level will always be a fundamental piece for the prevention and promotion of health because it has the capacity to face health situations that require teaching and education to the family or community.